ANALISIS EFEKTIVITAS DAN KONTRIBUSI PERUMDA PERGUDANGAN DAN ANEKA USAHA PEDARINGAN TERHADAP PENDAPATAN ASLI DAERAH KOTA SURAKARTA TAHUN 2014 – 2018 - Stela Maris Febriana Gea; Suharno Suharno; Fadjar Harimurti (Universitas Slamet Riyadi, 2020)
The government has a responsibility in digging every potential of the area in order to contribute to the acceptance of the local revenue independently. Local revenue can be said to be an influential source of acceptance in an area. If an area can properly compile the local revenue, financial availability to improve, develop, and organize regional autonomy will also be better too. This type of research is a descriptive analysis, with quantitative data types in the form of financial statements obtained from Perumda PAU Pedaringan and office of BPPKAD Surakarta. Data collection techniques using documentation, interviews, and library studies. This research analysis technique uses effectiveness analysis, contribution analysis, and calculation of ROA and ROE. The result of the effectiveness analysis in this study is the level of profit effectiveness Perumda PAU Pedaringan experienced a cycle of fluctuations from 2014 - 2018. The rate of profit contribution Perumda PAU Pedaringan was judges very less since 2014 - 2018. The level of health based on the calculation of ROA and ROE was reduced from 2014 - 2018.